2012
DOI: 10.1371/journal.pone.0030842
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mesenchymal Stem Cells on Cornea Wound Healing Induced by Acute Alkali Burn

Abstract: The aim of this study was to investigate the effects of subconjunctivally administered mesenchymal stem cells (MSCs) on corneal wound healing in the acute stage of an alkali burn. A corneal alkali burn model was generated by placing a piece of 3-mm diameter filter paper soaked in NaOH on the right eye of 48 Sprague-Dawley female rats. 24 rats were administered a subconjunctival injection of a suspension of 2×106 MSCs in 0.1 ml phosphate-buffered saline (PBS) on day 0 and day 3 after the corneal alkali burn. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 31 publications
3
123
0
18
Order By: Relevance
“…Further, we found that MSCs pretreated with IFN-g suppressed the infiltration of the damaged eye by CD14 + , CD80 + , and CD11b + Gr-1 + myeloid populations even more effectively than they inhibited infiltration by lymphoid cells. These results are in agreement with the findings of Yao et al [18], who showed that the number of CD68 + cells infiltrating the site of injury on day 7 was significantly lower in a group treated with MSCs [18]. In addition, the systemic injection of human MSCs significantly reduced the infiltration of neutrophils into the cornea on days 1 and 3 after injury in a rat model of a chemically burned eye [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, we found that MSCs pretreated with IFN-g suppressed the infiltration of the damaged eye by CD14 + , CD80 + , and CD11b + Gr-1 + myeloid populations even more effectively than they inhibited infiltration by lymphoid cells. These results are in agreement with the findings of Yao et al [18], who showed that the number of CD68 + cells infiltrating the site of injury on day 7 was significantly lower in a group treated with MSCs [18]. In addition, the systemic injection of human MSCs significantly reduced the infiltration of neutrophils into the cornea on days 1 and 3 after injury in a rat model of a chemically burned eye [19].…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that the curative effect of MSCs on corneal injury can consist partly in the epithelial transdifferentiation of MSCs [7,15] and in the suppression of corneal inflammation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has shown that systemically administered human MSCs reduced corneal inflammatory damage without engraftment by secreting anti-inflammatory factors in response to injury signals from the cornea [43] . Alternatively, MSCs may be administered locally to improve the concentration at the injured cornea through subconjunctival administration of MSCs [44] and through transplantation of MSCs with the amniotic membrane (AM) [45,46] and a hollow plastic tube onto the cornea [47] . Differentiation into corneal tissue LSC transplantation, the currently available treatment for severe corneal epithelium damage, has certain limitations.…”
Section: Msc Mobilization and Homingmentioning
confidence: 99%
“…However, the structural and functional restoration of alkali burn-injuries to the cornea remains a challenge, despite these therapies and thus prompting the search for novel treatment strategies [7][8][9]. A detailed study of regenerative processes under the influence of various drugs is a top priority of modern ophthalmology.…”
Section: Introductionmentioning
confidence: 99%